2017
DOI: 10.1089/hs.2016.0131
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Zoonotic Influenza A Virus Detection in Myanmar: Surveillance Practices and Findings

Abstract: We describe 2-season, risk-based, virological surveillance for zoonotic avian influenza in Myanmar and report the first detection of influenza A subtypes H5N6 and H9N2 in Myanmar. The study focused mainly on the live bird markets in border townships, where illegal poultry importation from China usually takes place. The objective was to enhance early warning for low pathogenic avian influenza A(H7N9) incursion. The study followed the guidelines of the Food and Agriculture Organization (FAO) of the United Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Several other examples highlight the effectiveness of ES used either on its own (for low pathogenic AIV (LPAIV)) in wild bird surveillance (Baek et al., 2010; Barbara et al., 2017; Perez‐Ramirez, Gerrikagoitia, Barral, & Hofle, 2010; Piaggio et al., 2012), or as a component (for HPAIV) (Bevins et al., 2014; Haynes et al., 2009; Khan et al., 2018) of large‐scale risk‐based surveillance systems in both high‐ (Deliberto et al., 2009; Grillo et al., 2015; Piaggio et al., 2012; Preskenis, Ladman, & Gelb, 2017) and low‐resourced (Gaidet et al., 2007; Gerloff et al., 2014; Khan et al., 2018; Ofula et al., 2013; Tun Win et al., 2017) settings, where broad‐scale surveillance proves logistically challenging (Grillo et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Several other examples highlight the effectiveness of ES used either on its own (for low pathogenic AIV (LPAIV)) in wild bird surveillance (Baek et al., 2010; Barbara et al., 2017; Perez‐Ramirez, Gerrikagoitia, Barral, & Hofle, 2010; Piaggio et al., 2012), or as a component (for HPAIV) (Bevins et al., 2014; Haynes et al., 2009; Khan et al., 2018) of large‐scale risk‐based surveillance systems in both high‐ (Deliberto et al., 2009; Grillo et al., 2015; Piaggio et al., 2012; Preskenis, Ladman, & Gelb, 2017) and low‐resourced (Gaidet et al., 2007; Gerloff et al., 2014; Khan et al., 2018; Ofula et al., 2013; Tun Win et al., 2017) settings, where broad‐scale surveillance proves logistically challenging (Grillo et al., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…For example, 4.2% of poultry were seropositive for IAVs in 2007 (Kyaw, 2008). In another survey, HPAI‐H5N1, HPAI‐H5N6 and LPAI‐H9N2 viruses were detected from the LBM in 2014–2016 (Tun Win et al., 2017). In this study, we reported IAV surveillance in MTN‐LBM and the genetic characteristics of IAVs isolated from the MTN‐LBM during 2017–2018.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, an influenza surveillance programme in LBMs in Shan state, northern Myanmar, identified LPAI‐H9N2 viruses (Lin et al., 2017). Another active surveillance in two major LBMs in Yangon and Mandalay reported H5N1, H5N6 and H9N2 viruses (Tun Win et al., 2017). Recently, HPAIV‐H5N1 (clade 2.3.2.1c) was reported in Tanintharyi, lower Myanmar, in 2017 (OIE, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Outbreaks occurred more than once in several States/Regions. The affected domestic poultry species included chickens, ducks, quails, and geese [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…From 2014 onwards, the LBVD detected Gs/GD/96-lineage H5N6 subtype HPAI viruses in samples both from border townships and from Mandalay and Yangon LBM [9] but not from farms. A number of these H5N6 positive samples were from ducks but the virus has not been associated with any reported outbreaks.…”
Section: Introductionmentioning
confidence: 99%